Habenula as a Neural Substrate for Aggressive Behavior - Gouveia, Flavia Venetucci; Ibrahim, George M. (Frontiers in Psychiatry, 2022)
Over the past decades, an ever growing body of literature has explored the anatomy, connections and functions of the habenula (Hb). It has been postulated that the Hb plays a central role in the control of the monoaminergic system, thus influencing a wide range of behavioural responses, and participating in the pathophysiology of a number of psychiatric disorders and neuropsychiatric symptoms, such as aggressive behaviours. Aggressive behaviours are frequently accompanied by restlessness and agitation, and are commonly observed in patients with psychiatric disorders, intellectual disabilities and neurodegenerative diseases of ageing. Recently, the Hb has been explored as a new target for neuromodulation therapies, such as deep brain stimulation, with promising results. Here we review the anatomical organization of the habenula and discuss several distinct mechanisms by which the Hb is involved in the modulation of aggressive behaviours, and propose new investigations for the development of novel treatments targeting the habenula to reduce aggressive behaviours.